Flannery O'Connor, Walker Percy, and the aesthetic of revelation - Sykes, John, 1952- (University of Missouri Press, 2007)
"Examining the writings of Flannery O'Connor and Walker Percy against the background of the Southern Renaissance from which they emerged, Sykes explores how the writers shared a distinctly Christian notion of art that led them to see fiction as revelatory but adopted different theological emphases and rhetorical strategies"--Provided by publisher